Online inquiry-based learning systems for argumentation: A systematic review - Jha, Nitesh Kumar; Bhowmik, Plaban Kumar; Bhagat, Kaushal Kumar (Educational Technology ＆ Society, 2024)
The aim of this study is to provide a current synthesis of Online Inquiry-Based Learning (OIBL) systems that use argumentation as a pedagogy. Data were collected from three databases: Scopus, Web of Science, and ERIC. The present review synthesized the findings of 73 studies from 2010 to June 2023. A qualitative content analysis was conducted to examine the inquiry-based systems regarding design features that support argumentation and learning outcomes. Four design features were identified: engaging students in unique and meaningful topics, providing visualization and scaffolding tools, collaborative inquiry in groups, and sharing and critiquing arguments. Most studies provided scaffolding and visualization support, while a few allowed students to engage in unique and meaningful topics. Most studies measured higher-level cognitive outcomes in contrast to lower-level outcomes. Future studies need to design systems for a more diverse population of students with improved collaboration support. In addition, this review identified a need to focus more on interdisciplinary topics rather than natural science.